Pengaruh Gaya Mengajar Guru Terhadap Motivasi Belajar Siswa Sekolah Dasar - Fitria Oktrisa; Melisya Anniva Putri; Adrias Adrias; Aissy Putri Zulkarnaini (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2025)
This study aims to specifically examine aspects of the learning process in elementary schools, which have an important role in building the academic foundation and character of students. The teacher's teaching style, which includes the way of delivering material, interaction, and strategies for creating a learning environment, is one of the determining factors for successful learning. The literature review method was used to analyze national literature, with the results showing a significant influence of the teacher's teaching style on elementary school students' learning motivation. Interactive and adaptive teaching styles have proven effective in increasing learning interest.